Multimedia Web-Based Constructivist Learning Application for Information Literacy Skills Development - Ismail, Mohd Nasir; Mamat, Nurfaezah (Journal of ICT in Education, 2019)
The purpose of this study is to design and develop a multimedia web-based constructivist learning application known as WebOPAC Self Training Tool with Guided Exploration (WSTTG) which is expected to train and access individual’s information literacy skills. This tool has been designed and developed according to the constructivist instructional design theories and constructivist instructional development model. The process design consists of four level processes which were component design, single path prototype, alpha version and beta version. The development process ended with four activities which were summative evaluation, final packaging, diffusion and adoption. Throughout the design and development process, there were two instructional designers and two subject matter experts were participated to review and evaluate the design components of the WSTTG. Three potential learners were also participated to evaluate the beta version prototype whether it is appropriately apply to their learning context. The repetition of reviewing the alpha and beta version prototypes lasted when there were no comments found during the final evaluation. Overall, all experts and learners were satisfied with the interface, surface characteristics, scenario, and instructional strategies used in the prototype after consideration on comments and suggestions have been made accordingly. This tool was recommended to be commercialized as an instructional strategy for library orientation program and to be used by both the librarians and library users for WebOPAC teaching and learning purposes. The design and development of this tool could be a guideline to future instructional designers, web developers and e-learning content specialist in developing a multimedia web-based constructivist application in various fields.